Optimization of the electrical discharge machining performance on titanium alloy by using statistical method - Maizatul Asnida, Hassan (2013)
This report will discuss about the aim of this project were to optimize the objective of machining parameters on Titanium alloy workpiece by using the Taguchi method. The machining characteristics such as the material removal rate (MRR), electrode wear rate (EWR), surface roughness (SR) have been recorded in and the analysis of the machining parameters using the copper as a tool or electrode at the cathode and titanium alloy as a workpiece at the anode with the two polarities selected. The method during this project is Design of experiment (DOE) which is an Analysis of Variance (ANOVA) and also the Taguchi method that has been used to define the optimization of single response characteristics. It is called as Taguchi Method that use to formulate the experimental layout, to analysis the effect of each parameter on the machining characteristics and to predict the optimal choice for each EDM parameter. The other, the result from the analysis using Taguchi method will compare with an RSM method to find the best DOE that can be used and from all comparison the most of the best method for the machining performance is RSM method. Thus, higher MRR from the analysis will give the result for the negative and positive copper which is at positive copper higher MRR suggested at peak current (22A), pulse-on time (180μs), pulse-off time (180μs) and servo voltage (95V), lower EWR at peak current (22A), pulse-on time (95μs), pulse-off time (240μs) and servo voltage (85V), and better SR at peak current (22A), pulse-on time (180μs), pulse-off time (240μs) and servo voltage (95V) is the goals and it taken separately in different phase of work during the experiment. The result of the negative copper also has been analysis and the best machining parameter for it also have been selected with the negative copper also come with the best combination of the parameter to optimize the machining performance where for the MRR the best combination of the parameter is at peak current (22A), pulse-on time (180μs), pulse-off time (240μs) and servo voltage (85V), the EWR at peak current (15A), pulse-on time (95μs), pulse-off time (180μs) and servo voltage (105V) is the best level and for the SR, the best combination at peak current (22A), pulse-on time (265μ), pulse-off time (240μs) and servo voltage (95V) is the best level of the parameter of the machining performance. The comparison between Taguchi and RSM method show that the most method that suitable to use is RSM method.